Preparation and Stability of Monascus Pigment Microcapsules by Complex Coacervation - CHEN Shiyun, SONG Chang, CHEN Yiling, HOU Siwen, LIANG Zihua, LI Wenlong, LÜ Xucong, NI Li (Shipin Kexue)
In order to improve the stability of Monascus pigments (MPs), gelatin and Arabic gum were used as wall materials, supplemented with transglutaminase (TGase) and hydroxypropyl-β-cyclodextrin, to prepare MP microcapsules by composite coagulation. Based on zeta potential and turbidity, the optimal gelatin-Arabic gum ratio and pH were determined to be 1:1 and 4.0, respectively. Furthermore, using response surface methodology, the optimal process conditions that provide maximum microencapsulation efficiency (85.06%) were established as follows: wall material concentration of 1.5%, core-to-wall ratio of 2.89:1, and coacervation time of 42 min. The solubility, storage stability, photostability and in vitro release characteristics of the microcapsules were characterized. The results showed that the microcapsules significantly improved the water solubility and storage stability of MPs and were the most stable under low temperature and room temperature conditions. The photodegradation processes of free and microencapsulated Monascus red and orange pigments followed the first-order kinetic model, while the photodegradation process of free and microencapsulated Monascus yellow pigments obeyed the zero-level kinetic model. Microencapsulation significantly improved the photostability of MPs. In addition, the microcapsules had good slow-release performance in simulated gastric fluid, and the release rate was significantly lower than in simulated intestinal fluid, indicating that the microcapsule system could well control the release of MPs in simulated gastrointestinal fluid.